AGLOMERASI DAN PERTUMBUHAN EKONOMI: PERAN KARAKTERISTIK REGIONAL DI INDONESIA - Sodik, Jamzani; Iskandar, Dedi (Jurnal Ekonomi & Studi Pembangunan, 2007)
The aim of this study is to examine the effect of agglomeration of regional economic growth across 26 provinces in Indonesia. The provincial pooling data for the period of 1994-2003 are regressed using generalized least square (GLS) method. Factors affecting the economic growth are considered such as agglomeration, labor force, inflation rates, openness rate of the provinces, and human capital. The study suggests the influence of three variables on the regional economic growth: labor force, inflation rates and the openness rate of the provinces; whereas the remaining two (agglomeration and human capital) are likely to have no effect.